Protective effects of oleuropein against renal injury oxidative damage in alloxan-induced diabetic rats; a histological and biochemical study - Hassan Ahmadvand; Gholamreza Shahsavari; Majid Tavafi; Shahrokh Bagheri; Mohamad Reza Moradkhani; Reza Mohammadrezaei Kkorramabadi; Peyman Khosravi; Maryam Jafari; Khadije Zahabi; Reza Eftekhar; Maryam Soleimaninejad; Sanaz Moghadam (Society of Diabetic Nephropathy Prevention, 2017)
Background: Oleuropein is a potent antioxidant and free-radical scavenger with antiinflammatory properties. Objectives: In the present study, we evaluated the protective effects of oleuropein on myeloperoxidase (MPO) activity, nitrite, urea, creatinine and glomerulosclerosis in alloxan-induced type 1 diabetic rats. Materials and Methods: Thirty Sprague-Dawley male rats were randomly divided into 3 groups: group 1 as control; group 2 as untreated diabetic; and group 3 as treated with oleuropein 15 mg/kg i.p daily. Diabetes was induced in the second and third groups by subcutaneous alloxan injection. After 48 days, the animals were anaesthetized and then the livers and kidneys were removed immediately and used fresh or kept frozen until MPO activity analysis. Blood samples were also collected before sacrificing to measure nitrite, urea, and creatinine. Kidney paraffin sections were prepared to estimate glomerular volume, leukocyte infiltration, and glomerulosclerosis. Results: Oleuropein significantly decreased leukocyte infiltration and glomerulosclerosis in the treated group compared with the diabetic untreated group. Oleuropein significantly decreased the levels of urea, nitrite, and creatinine in the treated group compared with the diabetic untreated group. Moreover, oleuropein significantly decreased MPO activity in the treated group compared with the diabetic untreated group. Conclusions: Oleuropein has antioxidative and antiatherogenic activities and exerts beneficial effects on inflammation and kidney function test and decreases diabetic complication in diabetic rats.